Neural mechanisms of mental schema: a triplet of delta, low beta/spindle and ripple oscillations. (19th February 2018) - Ohki, Takefumi; Takei, Yuichi
Abstract: Schemas are higher‐level knowledge structures that integrate and organise lower‐level representations. As internal templates, schemas are formed according to how events are perceived, interpreted and remembered. Although these higher‐level units are assumed to play a fundamental role in our daily life from an early age, the neuronal basis and mechanisms of schema formation and use remain largely unknown. It is important to elucidate how the brain constructs and maintains these higher‐level units. In order to examine the possible neural underpinnings of schema, we recapitulate previous work and discuss their findings related to schemas as the brain template. We specifically focused on low beta/spindle oscillations, which are assumed to be the key components of schemas, and propose that the brain template is implemented with a triplet of neural oscillations, that is delta, low beta/spindle and ripple oscillations. Abstract : Schemas are higher‐level knowledge structures that integrate and organise lower‐level representations. As internal templates, mental schemas are formed according to how events are perceived, interpreted and remembered. In order to examine the possible neural underpinnings of mental schema, we recapitulate previous work and discuss their findings related to schemas. Based on the literature reviewed, we suggest that mental schemas are underpinned by a triplet of neural oscillations, that is delta, low beta/spindle and ripple oscillations.